Correction: Arsenic trioxide exposure accelerates colon preneoplasic aberrant crypt foci induction regionally through mitochondrial dysfunction. Issue 2 (23rd February 2018) - Moulahoum, Hichem; Boumaza, Belkacem Mohamed Amine; Ferrat, Meriem
Abstract: Correction for 'Arsenic trioxide exposure accelerates colon preneoplasic aberrant crypt foci induction regionally through mitochondrial dysfunction' by Hichem Moulahoum et al., Toxicol. Res., 2017, DOI: 10.1039/C7TX00213K.